SJÖGREN'S SYNDROME - Özlem Deren,; Şehim Kutlay, (Archives of Rheumatology, 2003)
Sjögren's syndrome is characterized by dry eyes and dry mouth due to lymphocytic infiltrates of the lacrimal and salivary glands resulting in decreased production of saliva and tears. Females are affected 10 times more frequently than males. Sjögren's syndrome is divided into a primary form ( sicca complex) and a secondary form accompanying rheumatoid arthritis or occasionally another connective tissue disease. It has been suggested that the increased risk of lymphoma is particularly associated with primary Sjögren ‘s syndrome, especially of non-Hodgkin's type.